IMPROVING BASIC ENGLISH LANGUAGE IN ENTREPRENEURSHIP AND LITERACY PRACTICES USING LITERACY CLOUD: PENINGKATAN BERBAHASA INGGRIS DASAR ENTREPRENEURSHIP DAN PRAKTIK LITERASI MENGGUNAKAN LITERACY CLOUD - Ryandini, Elda Yulia; Novianti, Rini; Gibran, Sultan Rasya Naga; Riyadi, Anindhita Abidah (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: In education, it is vital for teachers to motivate students to engage their English skills through interactive speaking activities. Market day events, where students sell products using English, alongside digital platforms like literacy cloud, can significantly enhance interest in literacy. Objective: This initiative aims to equip first-grade students with foundational English language skills in entrepreneurship and literacy practices through the innovative literacy cloud platform. Method: Hosted at MI Wachid Hasjim in Surabaya, this activity involved 72 enthusiastic first-graders. The session kicked off with a lively sing-along of the English alphabet, followed by students introducing themselves by spelling their names. The curriculum included vocabulary relevant to entrepreneurship, an introduction to literacy cloud, and engaging reading practices with a selection of book titles. Results: The majority of students successfully pronounced and spelled their names in English, though some encountered difficulties with the letters